Supportive Programs Increase Medical Students' Research Interest and Productivity. (1st May 2006) - Zier, Karen; Friedman, Erica; Smith, Lawrence
Abstract : Background: Advances in biomedical research during the last decade have highlighted the necessity of attracting greater numbers of physicians to careers that include a research component. Physician participation in research is essential to increase the number of clinical and translational studies performed, as well as to educate the public about the importance of clinical trials and to assist in recruiting participants. We hypothesized that attractive research opportunities that included faculty mentoring, recognition of participation, and rewards for accomplishments would encourage medical student participation. Methods: The Medical Student Research Office was created at Mount Sinai School of Medicine in 1996 to develop structured research programs and advise students looking to undertake a research project. Data from students participating in the summer research program and Medical Student Research Day, from the research section of the Medical Student Performance Evaluation, were collected from 1996 to 2004. Results: For the last 4 years, the majority of medical students did research following the first year of school. Students did basic and clinical research, although most preferred clinically oriented or translational projects. Participation in Research Day and the number of publications suggest that interest is growing, including that by traditionally underrepresented groups. Conclusion: Although it is too early to assess the long-term effects, the research programs offered led to greater numbers of students who did research, including those in traditionally underrepresented groups. Moreover, students were highly satisfied with their experiences, with 80% feeling that it increased their interest in applying principles they learned to the practice of medicine.